Predictor of Successful DJ Stent Insertion in Advanced Cervical Cancer - Santosa, Kadek Budi; Prawira, Made Moniaga; Pramana, Ida Bagus Putra; Tirtayasa, Pande Made Wisnu; Yudiana, Wayan; Duarsa, Gede Wirya Kusuma; Oka, Anak Agung Gede (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Metastatic cervical cancer in the ureter may lead to obstructive uropathy due to mechanical ureteral blockage. The insertion of a double J (DJ) stent is a urinary diversion option that can be offered to the patients, but it becomes challenging due to the high rate of failures. AIM: The aim of the study was to determine the factors that predict the success of DJ stent insertion in obstructive uropathy due to advanced cervical cancer. MATERIALS AND METHODS: The patients studied were those with obstructive uropathy due to advanced cervical cancer from 2017 to 2020 in Sanglah General Hospital. The research subjects were divided into two groups: First were the samples of successful DJ stent insertions and the second were those that failed. In the analysis, the Chi-square tests were used for categorical data, while the independent t-tests were used for normally distributed data. Logistic regression analyses which involved both the univariate and multivariate were conducted to determine the factors that aided the success of DJ stent insertions. RESULTS: Retrograde stent insertion of DJ stents was conducted on 100 patients. Successful insertions were found in 57 patients (57%), while those that failed were observed in 43 subjects (43%). The results of multivariate regression analyses showed that low-grade hydronephrosis (odd ratios [OR] = 62.024; p = 0.000; confidence interval [CI] = 9.485–405.596), normal albumin levels (OR = 5.856; p = 0.018; CI = 1.359–25.243), lower Federation of Gynecology and Obstetrics (FIGO) staging (OR = 14.985; p = 0.007; CI = 2.108–106.536), and a history of radiotherapy (OR = 8.758; p = 0.005; CI = 1.943–39.477) were the significant factors for predicting the success of DJ stent insertions. CONCLUSION: Low-grade hydronephrosis, normal albumin levels, lower FIGO staging, and a history of radiotherapy are the strong factors for predicting the success of DJ stent insertions in obstructive uropathy due to advanced cervical cancer.